Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1089/dia.2008.0043
|View full text |Cite
|
Sign up to set email alerts
|

The Creation and Impact Evaluation of “Your Guide to Diet and Diabetes,” an Interactive Web-Based Diabetes Tutorial

Abstract: "Your Guide to Diet and Diabetes" filled a need for an easy-to-use website that addressed the issues of diet and diabetes. Based on the number of visits to the login page (n = 6,124) and number of individuals who answered demographic questions, the site was well received. While a smaller group of participants elected to complete the interactive knowledge and skills questions, responses to these questions demonstrated that participants obtained knowledge from the website. In particular, participants increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…10,15 Related psychosocial and behavioral variables were assessed in some studies: diabetes self-efficacy was measured in four trials, 15,18,19,21 diabetes knowledge was assessed in four studies, 16,22,24,25 and self-reported eating and exercise behaviors were assessed in three trials. 15,17,18 Web site usage patterns were assessed in several trials, some to explore participant interest or ease of accessing materials, 10,15,19,23,25 whereas other trials assessed correlations between Web site usage and study outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,15 Related psychosocial and behavioral variables were assessed in some studies: diabetes self-efficacy was measured in four trials, 15,18,19,21 diabetes knowledge was assessed in four studies, 16,22,24,25 and self-reported eating and exercise behaviors were assessed in three trials. 15,17,18 Web site usage patterns were assessed in several trials, some to explore participant interest or ease of accessing materials, 10,15,19,23,25 whereas other trials assessed correlations between Web site usage and study outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…15,17,18 Web site usage patterns were assessed in several trials, some to explore participant interest or ease of accessing materials, 10,15,19,23,25 whereas other trials assessed correlations between Web site usage and study outcomes. 10,16,20,21,24 Two studies compared very short-term outcomes (after only 2 weeks), 16 four studies compared outcomes at baseline and again 4, 6, or 12 weeks later. 17,21,22,23 Several studies compared outcomes 6-18 months from baseline, 10,14,15,[18][19][20] whereas the longest follow-up period was 2 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formats included static websites, decision aids,34 49 52 56 63 64 interactive websites,34–36 38–41 44–46 48 51 54–62 65–76 78 79 81 82 85 CD-ROM games or DVD,33 42 43 and email feedback programs 3437 47 52 53 77…”
Section: Resultsmentioning
confidence: 99%
“…Complications of T2D include renal failure, lower limb amputations, and heart disease [1]; such complications are associated with an individual’s self-management behaviors [2-4]. Regular preventative care is also essential to preventing comorbidities and maintaining a baseline level of health [5]. However, no greater than 75% of adults report receiving standard, recommended T2D preventive care, such as vaccinations, annual eye exams, at least an annual glycosylated hemoglobin (HbA1c) test, and regular foot examinations [1].…”
Section: Introductionmentioning
confidence: 99%